International Advances in Writing Research Cultures, Places, Measures - Bazerman, Charles; Dean, Chris; Early, Jessica Singer; Lunsford, Karen; Null, Suzie; Rogers, Paul; Stansell, Amanda (Open textbook library., 2012)
The thirty chapters in this edited collection were selected from the more than 500 presentations at the Writing Research Across Borders II Conference in 2011. With representatives from more than forty countries, this conference gave rise to the International Society for the Advancement of Writing Research. The chapters selected for this collection represent cutting edge research on writing from all regions, organized around three themes—cultures, places, and measures. The authors report research that considers writing in all levels of schooling, in science, in the public sphere, and in the workplace, as well as at the relationship among these various places of writing. The authors also consider the cultures of writing—among them national cultures, gender cultures, schooling cultures, scientific cultures, and cultures of the workplace. Finally, the chapters examine various ways of measuring writing and how these measures interact with practices of teaching and learning.Edited by Charles Bazerman, Chris Dean, Jessica Early, Karen Lunsford, Suzie Null, Paul Rogers, and Amanda Stansell.